The role of cerebellum in patients with late onset cervical/segmental dystonia?–Evidence from the clinic. Issue 11 (November 2015) - Batla, A.; Sánchez, M.C.; Erro, R.; Ganos, C.; Stamelou, M.; Balint, B.; Brugger, F.; Antelmi, E.; Bhatia, K.P.
Abstract: Background: There is evidence from animal studies, post-mortem pathology, functional imaging and neurophysiological studies to suggest that the cerebellum may be involved in the pathophysiology of dystonia. We sought to explore further the association of clinical and radiological abnormalities of the cerebellum in patients with dystonia. Methods: We retrospectively reviewed patients from our movement disorders research database, with predominant cervical dystonia who have been seen within last 6 months and had available routine magnetic resonance imaging (MRI). The clinical details including presence of cerebellar signs, imaging findings and results of investigations were recorded on a proforma. The results were analysed using percentages and means with standard deviation. Results: Out of 188 patients included 26 had evidence of cerebellar abnormality on neuroimaging. 17 patients showed cerebellar atrophy and 10 of these had cerebellar signs on examination. These patients were tested negative for common inherited ataxias. 9 patients had cerebellar lesions on MRI, reported as low grade tumour (n = 2), cerebellar infarct (n = 3), cyst (n = 2), white matter hyperintensity (n = 1) and ectopia (n = 1) out of these 4 had cerebellar signs. Conclusion: The findings from our study suggest that there may be overt clinical or radiological cerebellar involvement in 14% of cases with cervical/segmental dystonia. However, larger prospective studies are needed in this context. Graphical abstract: Highlights: Cerebellar atrophy or cerebellar lesions were seen in a 14% of cases with dystonia. Some but not all of these patients have cerebellar signs on examination. Some cases with fairly typical isolated cervical dystonia had cerebellar abnormalities on imaging. In addition to experimental evidence our results support the role of cerebellum in dystonia, even in clinical settings.